FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PERUMDA AIR MINUM PUSAT KOTA SURAKARTA - Miftakul Jannah; Kartika Hendra Ts; Riana R Dewi (Universitas Slamet Riyadi, 2020)
This research aims to test the involvement of users, user training and education programs, the support of top management, the ability of personal techniques on performance of accounting information system in the Waterworks Center of Surakarta City. The population in this study are all employees who use accounting information system in theWaterworks Center of Surakarta City. Sampling using a purposive sampling method with the employee criteria of his time for a minimum of one year. The independent variable in this study was the involvement of users, user training and education programs, the support of top management, the ability of the dependent variable for a personal technique in this study is accounting information system performance. This research method using multiple regression analysis to test the influence of free variables against variable directly. The results of this study indicate the program of training and education of users, top management support is a positive effect on performance of accounting information systems. While the involvement of users and personal skills have no effect on performance of accounting information systems.